Рlay therapy as an innovative technology in primary school (Pedagogy of Higher and Secondary Education, 2012)
Yakimenko S. Рlay therapy as an innovative technology in primary school.The article deals with the importance of play therapy as an innovative technology in primary school. The functions of the game, the place of play therapy for junior children school are disclosed.
Keywords: game; play therapy; innovative technology; educational process; playing activity